All that Glitters is not Cholecystitis. A Rare Presentation of Acute Pericarditis Mimicking Cholecystitis and Review of the Literature - Anna Garmpi; Christos Damaskos; Nikolaos Garmpis; Vasiliki Epameinondas Georgakopoulou; Vaios Vasileios Kaminiotis; Evangelos Diamantis; Alexandros Patsouras; Athanasios Syllaios; Dimitrios Dimitroulis (Acta Medica Lituanica, 2022)
Acute pericarditis is the most common inflammatory disorder of the pericardium, responsible for approximately 5% of visits to the emergency departments, concerning chest pain without myocardial infarction. We report a case of a 41-year-old man who presented to our hospital, complaining about retrosternal and epigastrium pain. The transthoracic echocardiogram showed pericardial effusion while the electrocardiogram and laboratory findings revealed acute pericarditis. An abdominal ultrasound revealed gallbladder edema. The pericardial effusion was treated with pericardial catheter insertion, diuretics, and nonsteroidal anti-inflammatory drugs. This case shows that acute pericarditis can be clinically presented with many ways, one of them being gallbladder edema. Furthermore, in this case-based review we present all cases of simultaneous appearance of pericarditis and acalculous cholecystitis or gallbladder edema.